Pelikula a video documentary on Philippine film : touchstones of excellence - Torre, Nestor U. (Tuklas sining series, 1993)
Explores the origins of local Philippine films and filmmaking in the late 19th century, up until the mid 20th century. Features notable films that have made their mark on Philippine moviegoers' psyche.